Antigens of Streptococcus mutans II. Characterization of an Antigen Resembling a Glycerol Teichoic Acid in Walls of Strain BHT - Vaught, Richard M. (1974)
Cold 10% trichloroacetic acid was used to extract antigens from purified cell walls of Streptococcus mutans BHT. Column chromatography on Biogel P-100 resolved two serologically reactive fractions (B and C). These fractions were ascertained to be relatively pure by recycling on Biogel P-100, Ouchterlony double-diffusion analysis, and immunoelectrophoresis. Fractions B and C demonstrated bands of absolute homology by double-diffusion but different mobilities by immunoelectrophoresis. Chemical analysis indicated that fraction B is a polysaccharide composed principally of rhamnose and galactose, with smaller amounts of glucose and glucosamine. Small quantities of glycerol and phosphorus also were found. Fraction C was composed mainly of galactose, glycerol, and phosphorus. Alkaline hydrolysis of this fraction yielded products typically released by the degradation of a glycerol teichoic acid, such as glycerol monophosphate, glycerol diphosphate, inorganic phosphorus, and several glycosyl glycerol phosphates. Diglycerol triphosphate was not detected. Side-group analysis revealed that glycerol was substituted by mono- and trigalactosyl moieties. Fraction C was deduced to contain 25 glycerol phosphate units per polymer length. Hapten inhibition studies revealed a β-galactoside as the probable hapten on this antigen. The BHT teichoic acid reacted strongly with FA-1 antiserum. It showed bands of homology with both BHT and FA-1 crude acid extracts upon double-diffusion, using antisera to either strain. The BHT teichoic acid also displayed immunoelectrophoretic behavior identical to one of the mobile FA-1 cell wall antigens, again using either serum to develop precipitin bands. It is concluded this antigen may possess a serotype-specific determinant for S. mutans serotype b.